Acute heart failure in patients with acute aortic syndrome: pathophysiology and clinical–prognostic implications. (27th July 2015) - Vagnarelli, Fabio; Corsini, Anna; Lorenzini, Massimiliano; Pacini, Davide; Ferlito, Marinella; Bacchi Reggiani, Letizia; Longhi, Simone; Nanni, Samuele; Norscini, Giulia; Cinti, Laura; Bugani, Giulia; Pasquale, Ferdinando; et al.
<x xml:space="preserve">Abstract</x> Aims Although acute heart failure (AHF) is a potential complication of acute aortic syndromes (AAS), its clinical details and management implications have been scarcely evaluated. This study aimed to assess prevalence, pathophysiological mechanisms, impact on treatment, and in‐hospital mortality of AHF in AAS. Methods and results Data were collected from a prospective AAS registry (398 patients diagnosed between 2000 and 2013). Patients with AHF were identified by the presence of dyspnoea as the presentation symptom or radiological signs of pulmonary congestion or cardiogenic shock, including patients with cardiac tamponade (CT). AHF frequency was 28% (Stanford type A 32% vs. type B 20%, P = 0.01). Four mechanisms leading to AHF were identified, alone or in combination: CT (26%), aortic regurgitation (25%), myocardial ischaemia (17%), and hypertensive crisis (10%). In type A patients, aortic regurgitation and CT were the most frequent mechanisms, whereas myocardial ischaemia and hypertensive crisis were the most frequent in type B patients. Although no difference was noted for diagnostic times, AHF at presentation led to a longer surgical delay in type A AAS. In‐hospital mortality was higher in patients with AHF compared with those without (34% vs. 17%, P < 0.001). After multivariable analysis, AHF was associated with increased risk of in‐hospital death (adjusted odds ratio 1.97, 95% confidence interval 1.14–3.36, P = 0.014). Conclusion AHF occurs in more than a quarter of patients with AAS of both type A and type B, is due to a variety of pathophysiological mechanisms, and is associated with increased surgical delay and in‐hospital mortality.